Efektifitas Pemberian Perlakuan Posisi Miring Kiri dan Upright Position terhadap Percepatan Kemajuan Persalinan Kala I Fase Aktif pada Ibu Inpartu - Ijabah, Nizzatul; Achyar, Khamidah; Kusuma, Inggar Ratna (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
The World Health Organization (WHO) reports that every day in 2017, around 810 women die from problems or complications of pregnancy and childbirth that are preventable. One of the complications in childbirth is prolonged labor, analysis of data from the World Health Organization shows that in 2017 prolonged labor was the direct cause of labor complications with an incidence of 69,000 or 2.8% of all maternal deaths worldwide. This study aims to determine the effectiveness of giving treatment in the left oblique position and the upright position on the progress of labor in the active phase of the first stage of labor in giving birth mothers. This type of research uses a literature study or literature review with a descriptive research method. This study uses 2 databases, namely PubMed and Google Scholar. The strategy search method for obtaining journals uses the keywords